Altered expression of insulin‐degrading enzyme and regulator of calcineurin in the rat intracerebral streptozotocin model and human apolipoprotein E‐ε4–associated Alzheimer's disease. Issue 1 (15th May 2019) - Delikkaya, Büşra; Moriel, Natalia; Tong, Ming; Gallucci, Gina; de la Monte, Suzanne M.
Abstract: Introduction: This study assesses insulin‐degrading enzyme (IDE) and regulator of calcineurin 1 (RCAN1) as potential mediators of brain insulin deficiency and neurodegeneration in experimental and human Alzheimer's disease (AD). Methods: Temporal lobes from Long Evans rats treated with intracerebral streptozotocin or vehicle and postmortem frontal lobes from humans with normal aging AD (Braak 0‐2), moderate (Braak 3‐4) AD, or advanced (Braak 5‐6) AD were used to measure IDE and RCAN mRNA and protein. Results: Intracerebral streptozotocin significantly increased IDE and RCAN mRNA and protein. In humans with apolipoprotein E (ApoE) ε3/ε4 or ε4/ε4 and AD, IDE was elevated at Braak 3‐4, but at Braak 5‐6, IDE expression was significantly reduced. RCAN1 mRNA was similarly reduced in ApoE ε4+ patients with moderate or severe AD, whereas RCAN1 protein declined with the severity of AD and ApoE ε4 dose. Discussion: The findings suggest that IDE and RCAN1 differentially modulate brain insulin signaling in relation to AD severity and ApoE genotype.